Comparisons among measurement approaches to determine blood loss with different environmental sanitary effects. Issue 1 (November 2021) - Sulastri,; Siregar, T N; Adlim, M; Hasanuddin,
Abstract: Labour and delivery are hazardous processes for bleeding. It will have complications, and even death for maternal because of overdue recognition and identification of the early signs of bleeding. Postpartum hemorrhage is still a problem and a major cause of maternal death. The definition, bleeding threshold, and method of assessing blood loss are still being debated today. This literature review aimed to determine the methods that had been used in measuring the amount of blood loss and risk to the mother. The review used Science Direct and Pubmed electronic online databases with related keyword searches. Measurement of blood loss was categorized into several methods, including visual estimation, direct measurement, gravimetry, and photometry. These methods were explained and then compared with various similar methods. Several studies indicated that measuring the amount of blood loss still often used conventional methods, even though this method was very improper and tends to underestimate blood loss. Several accurate and objective quantification methods had been introduced, but they were still very complicated, expensive, and time-consuming. Based on the review results, various types of blood loss measurement methods were displayed, but they were still not practical, accurate, and reliable. Researchers continue to carry out improvement research in finding methods so that postpartum hemorrhage can be prevented and treated.